2009
DOI: 10.1142/s0218495809000242
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Inclinations of Vocational Education Students: A Comparative Study of Male and Female Trainees in Iringa Region, Tanzania

Abstract: This study examined entrepreneurial inclinations among vocational training centres (VTCs) using a sample of 508 trainees from 12 VTCs in Iringa region, central Tanzania. A majority of VTC trainees have interest in starting own businesses, motivated primarily by the need to have control over their own lives. While gender and having taken entrepreneurship courses have no significant effects on start-up inclinations, perceived chances of getting a job and background of entrepreneurial family are positively associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 1 publication
2
36
0
Order By: Relevance
“…According to Corak andPiraino (2011) &Dunn andHoltz-Eakin (2000) second generation entrepreneurs are two to three times more likely to work in the same occupation as their fathers. A study by Olomi and Sinyamwale (2009) found that the students who had families which engaged in business had been better socialized to the entrepreneurial career and were likely to engage in starting their own businesses. Studies conducted in different countries like US (Crant, 1996); Singapore (Phan et al 2002); UK (Altinay et al 2012) and Malaysia (Tong et al 2011) gave similar results and found that entrepreneurial families or parents positively influence entrepreneurial career intentions in their children.…”
Section: Review Of Literature and Hypothesis Formulationmentioning
confidence: 99%
“…According to Corak andPiraino (2011) &Dunn andHoltz-Eakin (2000) second generation entrepreneurs are two to three times more likely to work in the same occupation as their fathers. A study by Olomi and Sinyamwale (2009) found that the students who had families which engaged in business had been better socialized to the entrepreneurial career and were likely to engage in starting their own businesses. Studies conducted in different countries like US (Crant, 1996); Singapore (Phan et al 2002); UK (Altinay et al 2012) and Malaysia (Tong et al 2011) gave similar results and found that entrepreneurial families or parents positively influence entrepreneurial career intentions in their children.…”
Section: Review Of Literature and Hypothesis Formulationmentioning
confidence: 99%
“…The results are consistent with previous empirical studies on the impact of family involvement in business and entrepreneurial intention. Olomi and Sinyamule (2009) find a positive association between entrepreneurial family background and entrepreneurial intention. Gerba (2012) finds that the mean score for students whose family members are involved in business is higher than those whose family members are not involved in business.…”
Section: Parents' Involvement In Business and The Entrepreneurial Intmentioning
confidence: 69%
“…Krueger (1993) also stipulated that young people whose families possess their own businesses are more likely to intend to start their own business. At the same time, Olomi and Sinyamule (2009) obtained positive association between background of entrepreneurial family and interest in entrepreneurial intention in Tanzania. Consequently, the following hypothesis is offered:…”
Section: Entrepreneurial Exposure Through Family Business and Intentionmentioning
confidence: 76%